Synergistic effect of Ag and WS2 on high temperature tribological performance of Ni3Al based composites - Mahto N.K.; Tyagi R.; Sinha S.K. (My University, 2025)
The present investigation was envisioned to explore the occurrence of a synergetic action between a combination of solid lubricants i.e., Ag and WS2 in providing effective lubrication over an extreme range of temperatures (RT to 800 °C) in Ni3Al based self-lubricating P/M processed composites. Results indicated a significant decrease in the coefficient of friction with the addition of solid lubricants either singly or in combination and Ni3Al-5Ag-5WS2 composite showed the lowest friction coefficient and wear rate due to synergetic action of Ag and WS2. At low temperatures, Ag and WS2 provided lubrication, whereas at high temperatures lubricious oxides like NiO, WO3, NiMoO4, Ag2MoO4, and Ag2Mo2O7 contributed in lowering the coefficient of friction as well as wear rate. © 2023 Elsevier Ltd